The Observed Relation between Stellar Mass, Dust Extinction, and Star Formation Rate in Local Galaxies - Zahid, H. Jabran (2013)
In this study, we investigate the relation between stellar mass, dust extinction, and star formation rate (SFR) using ∼150,000 star-forming galaxies from SDSS DR7. We show that the relation between dust extinction and SFR changes with stellar mass. For galaxies at the same stellar mass, dust extinction is anti-correlated with the SFR at stellar masses <1010 M☉. There is a sharp transition in the relation at a stellar mass of 1010 M☉. At larger stellar masses, dust extinction is positivelycorrelated with the SFR for galaxies at the same stellar mass. The observed relation between stellar mass, dust extinction, and SFR presented in this study helps to confirm similar trends observed in the relation between stellar mass, metallicity, and SFR. The relation reported in this study provides important new constraints on the physical processes governing the chemical evolution of galaxies. The correlation between SFR and dust extinction for galaxies with stellar masses >1010 M☉ is shown to extend to the population of quiescent galaxies suggesting that the physical processes responsible for the observed relation between stellar mass, dust extinction, and SFR may be related to the processes leading to the shutdown of star formation in galaxies.